State Authority in Regulating International Business Transactions: Between Sovereign Regulatory Power and International Commercial Norms - Muhammad Rafly Faeruz Zaman; Wafda Vivid Izziyana (Justice Law Review, 2026)
This article examines the dynamics of state authority in regulating international business transactions at the intersection between sovereign regulatory power and international commercial norms. On one hand, the state holds a constitutional mandate to establish regulations that ensure legal certainty, protect national interests, and maintain domestic economic stability. On the other hand, economic globalization demands harmonization with commercial norms shaped by lex mercatoria, multilateral trade agreements, and transnational contractual standards. Tensions arise when domestic policies that are protective or interventionist are perceived as potential barriers to the flow of international investment and trade. Through a normative juridical approach and comparative analysis, this article explores how states navigate their regulatory space to preserve normative sovereignty while remaining aligned with international commercial principles emphasizing efficiency, predictability, and non-discrimination. The findings indicate that the effectiveness of domestic regulation in international business transactions depends largely on the ability of states to adopt adaptive, proportional, and internationally consistent regulatory models. Thus, the dialogue between sovereign regulatory power and international commercial norms is not merely a site of conflict, but an opportunity to build a more responsive national legal regime in the face of global economic dynamics.